Composite catalytic layer membrane electrode based on heterogeneous catalyst and preparation method and application thereof

By using a composite catalytic layer film electrode with heterogeneous catalyst in fuel cells, combining carbon-based materials and metal oxide-supported platinum-based metal nanocluster catalysts, the problem of electrochemical corrosion under high potential is solved, and significantly improved The corrosion resistance and electrical energy output efficiency of fuel cells.

CN119252998APending Publication Date: 2025-01-03WUXI SHENGXIN HYDROGEN ENERGY TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310808370.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-03
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The cathode catalytic layer of the existing proton exchange membrane fuel cell is prone to electrochemical corrosion under high electric potential, resulting in the collapse of the catalytic layer skeleton and the shedding of metal nanoclusters, reducing the life of the fuel cell and the power generation efficiency.

Method used

Using a composite catalytic layer film electrode based on heterogeneous catalysts, combined with carbon-based materials to support platinum-based metal nanocluster catalysts and metal oxide-loaded platinum-based metal nanocluster catalysts, a multi-layer structure cathode catalytic layer is constructed to enhance the electricity with high potential resistance. Chemical corrosion performance while maintaining excellent electrical energy output performance.

Benefits of technology

It significantly improves the electrochemical corrosion resistance of the membrane electrode under high potential, maintains high electrical energy output power density, extends the life of the fuel cell, and is better than membrane electrodes that use carbon-based materials to load platinum-based metal nanocluster catalysts alone.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252998A_ABST
    Figure CN119252998A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of fuel cells, and particularly relates to a composite catalyst layer membrane electrode and a preparation method and application thereof. The composite catalyst layer membrane electrode is composed of a proton exchange membrane, a cathode catalyst layer and an anode catalyst layer, the cathode catalyst layer and the anode catalyst layer cover the surfaces of the two sides of the proton exchange membrane respectively, the cathode catalyst layer is of a multi-layer structure, and the multi-layer structure comprises at least one catalyst layer which is based on a carbon-based material loaded platinum-based metal nano-cluster catalyst. The at least one catalyst layer is a catalyst layer based on a metal oxide loaded platinum-based metal nano-cluster catalyst, and the platinum-based metal nano-cluster is platinum or platinum-based alloy nano-cluster. The catalytic layer based on the metal oxide loaded platinum-based metal nano-cluster catalyst in the composite catalytic layer membrane electrode remarkably inhibits electrochemical corrosion of the catalytic layer based on the carbon-based material loaded platinum-based metal nano-cluster catalyst, and meanwhile, the membrane electrode is endowed with excellent catalytic performance and excellent mass transfer performance and conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of fuel cells, and in particular relates to a composite catalytic layer membrane electrode based on a heterogeneous catalyst, a preparation method thereof, and an application thereof in a proton exchange membrane fuel cell. Background Art

[0002] A fuel cell is a power generation device that converts chemical energy into electrical energy. It plays an important role in the development and utilization of new energy and environmental protection. The membrane electrode is a key material or device for fuel cells. Its catalytic activity, stability, and reactant diffusion performance are crucial to the power generation efficiency and life performance of fuel cells. The cathode catalyst layer of the membrane electrode of the proton exchange membrane fuel cell currently in practical use is usually composed of a platinum-based metal nanocluster catalyst supported on a carbon-based material and a fluoroalkylsulfonic acid ion migration material. This type of material has the advantages of good conductivity and excellent mass transfer performance.

[0003] However, under the working conditions of fuel cells, carbon-based materials are prone to electrochemical corrosion, resulting in the collapse of the catalyst layer skeleton, the aggregation or shedding of metal nanoclusters, which significantly reduces the performance and life of the membrane electrode, thereby shortening the life of the fuel cell. Especially under the start-up and shutdown conditions of the fuel cell, due to the presence of a hydrogen-oxygen interface on the anode side of the membrane electrode, a very high potential (~1.5V) will appear on the cathode side. This will cause severe electrochemical corrosion of the platinum-based metal nanocluster catalyst supported by the highly active carbon-based material, causing the membrane electrode cathode catalyst layer based on such catalysts to be destroyed at a higher speed and degree. Therefore, how to improve the anti-electrochemical corrosion performance of the cathode catalyst layer under high potential, and maintain its excellent catalytic activity and good mass transfer efficiency for the oxygen reduction reaction, so as to improve the output power density and life of the fuel cell, has long been a challenging issue in the field of fuel cells.

[0004] In recent years, some progress has been made in the research and development of metal oxide-supported platinum-based metal nanocluster fuel cell catalysts. For example, the oxide-supported platinum-based metal nanocluster catalysts previously developed by the inventors of this patent have the advantages of high Pt-based metal nanocluster loading, large dispersion, high catalytic activity for oxygen reduction reaction, and outstanding oxidation resistance and electrochemical corrosion performance (Wang Yuan et al., Chinese invention patent CN201810720349.0; J. Power Sources, 2020, 446, 227332). However, the fuel cell membrane electrode prepared by replacing the carbon-based material-supported platinum-based metal nanocluster catalyst with a metal oxide-supported platinum-based metal nanocluster catalyst still needs to be further improved in terms of mass transfer performance and power output power density.

[0005] To solve the above problems, the present invention provides a novel composite catalytic layer fuel cell membrane electrode based on heterogeneous catalysts. The electrical energy output power density of this type of membrane electrode is close to or even better than that of a membrane electrode prepared using only carbon-based materials loaded with platinum-based metal nanocluster catalysts, and its resistance to electrochemical corrosion under high potential is far better than the latter, providing a new idea and feasible solution to solving the above problems. Summary of the invention

[0006] In view of the technical problems existing in the background technology, the present invention provides a composite catalytic layer membrane electrode based on a heterogeneous catalyst with excellent electrochemical corrosion resistance and excellent power output performance, a preparation method thereof, and its application in a proton exchange membrane fuel cell.

[0007] The technical solution adopted by the present invention is as follows: a composite catalyst layer membrane electrode based on a heterogeneous catalyst, which is composed of a proton exchange membrane and a cathode catalyst layer and an anode catalyst layer respectively covering the surfaces on both sides thereof, wherein the cathode catalyst layer has a multilayer structure, which includes at least one catalyst layer based on a carbon-based material-loaded platinum-based metal nanocluster catalyst, and also includes at least one catalyst layer based on a metal oxide-loaded platinum-based metal nanocluster catalyst, wherein the platinum-based metal nanocluster is a platinum or platinum-based alloy nanocluster.

[0008] Furthermore, the cathode catalyst layer of the composite catalyst layer membrane electrode of the present invention may have a double-layer structure, wherein one layer is a catalyst layer based on the carbon-based material-loaded platinum-based metal nanocluster catalyst located above the proton exchange membrane, and the other layer is a catalyst layer based on the metal oxide-loaded platinum-based metal nanocluster catalyst located above the above-mentioned catalyst layer. Figure 1 A structure of the composite catalyst layer membrane electrode is given. The structure of this membrane electrode is different from the structure of the membrane electrode based on the carbon-based material loaded platinum-based metal nanocluster catalyst layer in the past ( Figure 2 ).

[0009] Furthermore, the anode catalyst layer of the composite catalyst layer membrane electrode of the present invention is a catalyst layer based on a carbon-based material loaded with a platinum-based metal nanocluster catalyst, and the anode catalyst layer may also contain an iridium oxide catalyst or an iridium oxide-metal iridium composite catalyst.

[0010] Furthermore, the above-mentioned catalytic layer based on carbon-based materials loaded with platinum-based metal nanocluster catalysts is composed of a composite of carbon-based materials loaded with platinum-based metal nanocluster catalysts and fluoroalkyl sulfonic acid, and the catalytic layer based on metal oxides loaded with platinum-based metal nanocluster catalysts is composed of a composite of metal oxides loaded with platinum-based metal nanocluster catalysts and fluoroalkyl sulfonic acid.

[0011] Furthermore, the metal oxide-supported platinum-based metal nanocluster catalyst is a metal oxide nanoparticle-supported platinum-based metal nanocluster catalyst, and the average particle size of the metal oxide nanoparticles is 5-200 nanometers.

[0012] Furthermore, the metal oxide nanoparticles are oxides containing at least one of the elements In, Ti, Sn, Sb, Co, and Cu, and the platinum-based alloy nanoclusters are alloy nanoclusters formed by Pt and at least one of the elements In, Ru, and Cu.

[0013] Furthermore, the metal oxide is indium oxide or a composite oxide formed by indium and at least one of Ti, Sn, Sb, Cu, and Co elements.

[0014] Furthermore, the metal oxide-supported platinum-based metal nanoclusters may be indium oxide-supported platinum-indium alloy nanoclusters.

[0015] Furthermore, in the above metal oxide-supported platinum-based metal nanocluster catalyst, on the same metal oxide particle, the average distance between adjacent Pt-based metal nanoclusters in direct contact with the metal oxide particle is less than 2 nanometers, preferably less than 0.6 nanometers.

[0016] The cathode catalytic layer of the composite catalytic layer membrane electrode of the present invention may also have a three-layer structure, wherein one layer is a catalytic layer based on metal oxide nanoparticles loaded with platinum-based metal nanocluster catalysts located above the proton exchange membrane, one layer is a catalytic layer based on carbon-based materials loaded with platinum-based metal nanocluster catalysts located thereon, and the other layer is a catalytic layer based on metal oxide nanoparticles loaded with platinum-based metal nanocluster catalysts located above the catalytic layer based on carbon-based materials loaded with platinum-based metal nanocluster catalysts.

[0017] In the composite catalytic layer membrane electrode of the present invention, the platinum content in the metal oxide-supported platinum-based metal nanocluster catalyst is 20-70%, and the average particle size of the platinum-based metal nanocluster is 1.5 to 5 nanometers.

[0018] The thickness of the catalytic layer based on the metal oxide supported platinum-based metal nanocluster catalyst is 0.05-20 microns, preferably 0.1-10 microns, and more preferably 0.5-5 microns.

[0019] The platinum content of the catalyst layer based on the metal oxide supported platinum-based metal nanocluster catalyst is 0.01-1 mg / cm 2 , preferably 0.03-0.5 mg / cm 2 , more preferably 0.05-0.4 mg / cm 2 .

[0020] The present invention also provides a method for preparing a composite membrane electrode based on heterogeneous catalysts, which comprises coating or spraying the carbon-based material-supported platinum-based metal nanocluster catalyst or the metal oxide nanoparticle-supported composite membrane electrode on the surface of the proton exchange membrane in sequence according to the needs of the membrane electrode structure. Platinum-based Catalytic layer of metal nanocluster catalysts.

[0021] Furthermore, in the above preparation method, the slurry used in the coating or spraying is basically composed of a dispersant, a metal oxide nanoparticle carrier Platinum-based The catalyst is composed of a metal nanocluster catalyst or a carbon-based material loaded with a platinum-based metal nanocluster catalyst and a fluoroalkylsulfonic acid proton migration material.

[0022] Furthermore, in the above preparation method, the dispersant is selected from at least one of water and alcohol, the alcohol has a carbon number of 1 to 8, and is preferably at least one of ethanol, propanol, and butanol.

[0023] The composite catalytic layer membrane electrode based on heterogeneous catalyst prepared by the preparation method of the present invention also belongs to the protection scope of the present invention.

[0024] The fuel cell based on the composite catalytic layer membrane electrode based on the heterogeneous catalyst of the present invention also falls within the protection scope of the present invention.

[0025] Compared with the prior art, the technical advantages of the present invention are:

[0026] The present invention selects to utilize a metal oxide-supported platinum-based metal nanocluster catalyst, and by constructing a multi-layer catalyst layer structure, a catalyst layer based on a metal oxide-supported platinum-based metal nanocluster catalyst and a catalyst layer based on a carbon-based material-supported platinum-based metal nanocluster catalyst are composited to form a composite catalyst layer membrane electrode based on a heterogeneous catalyst. Compared with a membrane electrode prepared using only a carbon-based material-supported platinum-based metal nanocluster catalyst, the composite catalyst layer membrane electrode of the present invention has better resistance to electrochemical corrosion under high potential, and at the same time, the power output efficiency of the composite catalyst layer membrane electrode is not significantly reduced due to the presence of a catalyst layer based on a metal oxide-supported platinum-based metal nanocluster catalyst, and its power output power density is close to or even better than a membrane electrode prepared using only a carbon-based material-supported platinum-based metal nanocluster catalyst. For example, the results of Example 1 and Comparative Example 1 show that when the Pt loading of the cathode and anode of the membrane electrode is the same and the type of Pt / C catalyst (Pt / C-TKK, model: TEC10E50E) is the same, the composite catalyst layer membrane electrode of Example 1 of the present invention exhibits higher power output density and better high potential corrosion resistance than the membrane electrode using only Pt / C catalyst as the cathode catalyst. After cyclic voltammetry aging treatment (potential scanning range: 1.0-1.5V), the composite catalyst layer membrane electrode prepared in Example 1 of the present invention has a higher power output density and better high potential corrosion resistance at 400mA / cm 2The potential decay under current density is 150mV, while the membrane electrode based on Pt / C catalyst cathode catalyst layer in comparative example 1 is 400mA / cm 2 The potential decay at the current density was 257 mV.

[0027] The results of Example 2 and Comparative Example 3 show that when the Pt loading of the cathode and anode of the membrane electrode is the same and the type of Pt / C catalyst (Pt / C-BY, Suzhou Boya Original Nanotechnology Co., Ltd., Pt content is 75wt.%) is the same, compared with the membrane electrode based on the Pt / C catalyst cathode catalyst layer of Comparative Example 2, the composite catalyst layer membrane electrode of Example 2 of the present invention exhibits basically the same initial power density and better electrochemical corrosion resistance. After cyclic voltammetry aging treatment (potential scanning range: 1.0-1.5V), the composite catalyst layer membrane electrode prepared in Example 2 of the present invention has a substantially consistent initial power density and better electrochemical corrosion resistance. 2 and 1500mA / cm 2 The potential decays at current density were 33mV and 83mV respectively, while the membrane electrode based on the Pt / C catalyst cathode catalyst layer in the control example 3 was 400mA / cm 2 and 1500mA / cm 2 The potential decay under the current density is 59mV and 137mV respectively. After the above aging treatment, the power density of the electric energy output of the composite catalyst layer membrane electrode of the present invention is much higher than that of the membrane electrode based on the Pt / C catalyst cathode catalyst layer.

[0028] The reasons why the membrane electrode of hydrogen-oxygen fuel cell is easily corroded and the performance decays quickly under high potential are relatively complex. One of the important reasons is that the carbon-based carrier is easily oxidized under high potential. In the composite catalyst layer membrane electrode of the present invention, the platinum content and thickness of the catalyst layer based on the metal oxide-supported platinum-based metal nanocluster catalyst are much smaller than the platinum content and thickness of the catalyst layer based on the carbon-based material-supported platinum-based metal nanocluster catalyst, but the high potential electrochemical corrosion resistance of the composite catalyst layer membrane electrode is significantly enhanced. In addition, from the results of Comparative Example 1 and Reference Example 2, it can be seen that the structure of the multilayer cathode catalyst layer composed of the catalyst layer based on the metal oxide-supported platinum-based metal nanocluster catalyst and the catalyst layer based on the carbon-based material-supported platinum-based metal nanocluster catalyst in the composite catalyst layer membrane electrode of the present invention plays a key role in improving the high potential electrochemical corrosion resistance of the membrane electrode. The effect of the technical solution of the present invention cannot be inferred based on previous experience.

[0029] The above results show that the catalytic layer based on metal oxide-supported platinum-based metal nanocluster catalyst in the composite catalytic layer membrane electrode of the present invention significantly inhibits the electrochemical corrosion of the catalytic layer based on carbon-based material-supported metal nanocluster catalyst, while giving the membrane electrode excellent catalytic performance, as well as outstanding mass transfer performance and conductivity. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The schematic diagram of the structure of a composite catalyst layer membrane electrode based on heterogeneous catalysts of the present invention. Among them, ① is a proton exchange membrane, ② is a catalyst layer based on Pt / C catalyst, ③ is a catalyst layer based on metal oxide-supported platinum-based metal nanocluster catalyst, and ④ is an anode catalyst layer based on Pt / C and other catalysts. ② and ③ constitute a double-layer composite membrane cathode catalyst layer.

[0031] Figure 2 This is a schematic diagram of the structure of a commercial membrane electrode in the past. ① is the proton exchange membrane, ② is the cathode catalyst layer based on Pt / C catalyst, and ③ is the anode catalyst layer based on Pt / C and other catalysts.

[0032] Figure 3 The performance comparison of the composite catalyst layer membrane electrode based on heterogeneous catalyst prepared by using Pt / C-TKK catalyst and indium oxide supported platinum indium alloy nanocluster catalyst (PtIn / In2O3) in Example 1 and the membrane electrode based on Pt / C-TKK catalyst with conventional structure prepared in Control Example 1 is the polarization curves of the two membrane electrodes before and after electrochemical aging. The experimental conditions of the electrochemical aging are cyclic voltammetry scans in the potential range of 1-1.5V for 5000 times.

[0033] Figure 4 The performance comparison of the composite catalyst layer membrane electrode based on heterogeneous catalyst prepared in Example 1 and the membrane electrode prepared with Pt / C-TKK and PtIn / In2O3 mixture as cathode catalyst in Control Example 2 is shown in the polarization curves of the two membrane electrodes before and after electrochemical aging. The experimental conditions of the electrochemical aging are 5000 cyclic voltammetric scans in the potential range of 1-1.5V.

[0034] Figure 5 The performance comparison of the composite catalyst layer membrane electrode based on heterogeneous catalyst prepared by using Pt / C-BY catalyst and indium oxide supported platinum indium alloy nanocluster catalyst (PtIn / In2O3) in Example 2 and the membrane electrode based on Pt / C-BY catalyst with conventional structure prepared in Control Example 3 is the polarization curves of the two membrane electrodes before and after electrochemical aging. The experimental conditions of the electrochemical aging are 5000 cyclic voltammetry scans in the potential range of 1-1.5V. DETAILED DESCRIPTION

[0035] The present invention is further described below in conjunction with specific examples, but the present invention is not limited to the following examples. The methods described are conventional methods unless otherwise specified. The raw materials described can be obtained from public commercial channels unless otherwise specified.

[0036] Example 1: Preparation and performance test of composite catalyst membrane electrode based on heterogeneous catalyst of indium oxide supported platinum indium alloy nanocluster catalyst (PtIn / In2O3) and platinum carbon catalyst (Pt / C-TKK)

[0037] Step 1: Preparation of a spray slurry based on indium oxide-supported platinum indium alloy nanocluster catalyst (PtIn / In2O3)

[0038] Add 0.04 g indium oxide-supported platinum indium alloy nanocluster catalyst (PtIn / In2O3, Suzhou Boya Original Nanotechnology Co., Ltd., Pt content 42%, average spacing of PtIn alloy nanoclusters less than 1 nm, average particle size of In2O3 nanoparticles 19 nm, average particle size of PtIn alloy nanoclusters 3.4 nm) into a beaker, 0.5 mL of water, 5 mL of isopropanol, and 0.05 mL of Nafion solution (mass percentage concentration of 5%). Ultrasonic treatment was performed for 1 hour to obtain a spray slurry based on indium oxide-supported platinum indium alloy nanocluster catalyst (PtIn / In2O3).

[0039] Step 2: Preparation of a spray slurry based on a platinum-carbon catalyst (Pt / C-TKK)

[0040] 0.12 g of Pt / C-TKK catalyst (Pt / C-TKK, Tanaka Precious Metals Co., Ltd., model: TEC10E50E, Pt mass percentage: 50%), 1.1 mL of water, 4.3 mL of isopropanol, and 1.03 mL of Nafion solution (mass percentage concentration of 5%) were added to a beaker and ultrasonically treated for 1 hour to prepare a spray slurry based on platinum carbon catalyst (Pt / C-TKK).

[0041] Step 3: membrane electrode preparation:

[0042] (1) Preparation of cathode catalyst layer: First, a catalyst layer based on Pt / C-TKK catalyst prepared in step 2 was sprayed on one side of a proton exchange membrane (8 μm, Gore). After drying, an X-ray fluorescence spectrometer was used to measure the Pt content of the catalyst layer to be 0.35 mg / cm 2 Then, a catalyst layer based on PtIn / In2O3 catalyst was sprayed on the surface of the catalyst layer based on Pt / C-TKK catalyst using the slurry based on PtIn / In2O3 catalyst prepared in step 1. After drying, the platinum content of the catalyst layer based on PtIn / In2O3 catalyst was measured by X-ray fluorescence spectrometer to be 0.05 mg / cm 2 , that is, the double-layer cathode catalyst layer of the membrane electrode is obtained.

[0043] (2) Preparation of anode catalyst layer: Using the spray slurry based on Pt / C-TKK catalyst prepared in step 2, a thin film based on Pt / C-TKK catalyst is sprayed on the other side surface of the Gore proton exchange membrane as an anode catalyst membrane, and after drying, a composite catalyst layer membrane electrode (CCM) based on heterogeneous catalyst of the present invention is obtained. The total platinum content of the membrane electrode measured by X-ray fluorescence is 0.5 mg / cm 2 , that is, the platinum loading of the anode catalyst layer is 0.1 mg / cm 2 .

[0044] The X-ray fluorescence test working curve used in the experiment has been calibrated using the weighing method and inductively coupled plasma spectrometer.

[0045] The results of membrane electrode cross-section tests using an electron microscope showed that in the cathode double-layer catalytic membrane, the thickness of the catalytic layer based on the Pt / C-TKK catalyst was 9 μm, and the thickness of the catalytic layer based on the PtIn / In2O3 catalyst was 0.7 μm.

[0046] Step 4: Membrane electrode performance test:

[0047] The membrane electrode (CCM) prepared in step 3 above and carbon paper (produced by Freudenberg, model H24CX483) were assembled into a single cell for testing and the membrane electrode polarization curve and electrochemical aging resistance performance tests were carried out. The polarization curve test conditions are: hydrogen with a relative humidity (RH) of 100% is passed to the anode, air with a RH of 100% is passed to the cathode, and the battery temperature is 80°C. The anode excess coefficient is 1.5, the cathode excess coefficient is 2.5, and the back pressure is 150kPa. The durability test conditions are: hydrogen with a RH of 100% is passed to the anode, nitrogen with a RH of 100% is passed to the cathode, and the battery temperature is 80°C. Using a triangular wave method, the membrane electrode cathode was scanned for 5000 cycles in the potential range of 1.0 to 1.5V, with a scan rate of 500mV / s. The polarization curve of the membrane electrode is as shown Figure 3 As shown in Figure 2, the performance degradation after electrochemical aging treatment is as follows: Figure 3 And as shown in Table 1.

[0048] Comparative Example 1: Preparation and Performance Test of Membrane Electrode with Pt / C-TKK as Cathode Catalyst

[0049] Step 1, preparation of Pt / C-TKK catalyst slurry:

[0050] The spray slurry based on Pt / C-TKK catalyst was prepared according to the method of step 2 in Example 1.

[0051] Step 2: membrane electrode preparation:

[0052] (1) Preparation of cathode catalyst layer: Using the Pt / C-TKK catalyst spray slurry prepared in step 1, a Pt / C-TKK catalyst film was sprayed on one side of a proton exchange membrane (8 μm, Gore). After drying, an X-ray fluorescence spectrometer was used to measure the Pt content of the catalyst layer to be 0.35 mg / cm 2 Then, a Pt / C-TKK catalyst film was sprayed on the surface to make the Pt content of the cathode catalyst layer 0.4 mg / cm 2 .

[0053] (2) Preparation of anode catalyst layer: The anode catalyst layer was prepared according to the method of Example 1.

[0054] Step 3: Membrane electrode performance test:

[0055] The polarization curve and electrochemical aging resistance of the membrane electrode prepared in this experiment were tested according to the method and conditions of Example 1. The polarization curve of the membrane electrode is as follows: Figure 3 As shown in Figure 2, the performance degradation after electrochemical aging treatment is as follows: Figure 3 And as shown in Table 1.

[0056] By comparing the experimental results of Example 1 and Control Example 1, it can be seen that when the Pt loading of the cathode and anode of the membrane electrode is the same and the type of Pt / C catalyst (Pt / C-TKK) ​​is the same, the composite catalyst layer membrane electrode prepared in Example 1 of the present invention exhibits higher power output density and better high potential corrosion resistance than the membrane electrode based on the cathode catalyst layer of the Pt / C-TKK catalyst ( Figure 3 After cyclic voltammetry aging treatment (potential scanning range: 1.0-1.5V), the composite catalyst layer membrane electrode prepared in Example 1 of the present invention has a potential scanning range of 1.0-1.5V at 400mA / cm 2 The potential decay under current density is 150mV, while the membrane electrode based on Pt / C catalyst cathode catalyst layer in comparative example 1 is 400mA / cm 2 The potential decay at the current density was 257 mV (Table 1).

[0057] Comparative Example 2 Preparation and Performance Test of Membrane Electrode with Pt / C-TKK and PtIn / In2O3 Mixture as Cathode Catalyst

[0058] Step 1, cathode catalyst layer spray slurry preparation: add 0.118g Pt / C-TKK catalyst (Pt / C-TKK, Tanaka Precious Metals Co., Ltd., platinum mass percentage of 50%) and 0.017g PtIn / In2O3 catalyst used in Example 1 into a beaker, mix well, add 1.1mL water, 4.3mL isopropanol, 1.02mL Nafion solution (mass percentage concentration of 5%), ultrasonic treatment for 1 hour, to obtain the cathode catalyst layer spray slurry.

[0059] Step 2: Membrane electrode preparation and testing:

[0060] The cathode catalyst layer spray slurry prepared in step 1 was substituted for the cathode catalyst layer spray slurry based on Pt / C-TKK catalyst in reference example 1, and the cathode catalyst membrane was prepared according to the method and steps of reference example 1. The anode catalyst membrane was prepared by the same method and conditions as in Example 1. The performance of the prepared membrane electrode was tested by the same method and test conditions. The polarization curve of the membrane electrode is shown in FIG. Figure 4 As shown in Figure 2, the performance degradation after electrochemical aging treatment is as follows: Figure 4 As shown in Table 2. Figure 4 It can be seen that the initial power output efficiency of the composite catalytic layer membrane electrode of the present invention prepared in Example 1 is much higher than that of the membrane electrode in Control Example 2 which uses a mixture of the same Pt / C-TKK and PtIn / In2O3 catalysts as the cathode catalyst, and its potential attenuation after electrochemical aging treatment is much smaller than the latter.

[0061] By comparing the experimental results of Example 1 and Control Example 2, it can be seen that the performance of the composite catalytic layer membrane electrode prepared in Example 1 of the present invention is much better than the performance of the membrane electrode using a mixture of Pt / C-TKK and PtIn / In2O3 as the cathode catalyst, which fully demonstrates that the multilayer structure of the composite catalytic layer membrane electrode of the present invention has the special performance of inhibiting the electrochemical corrosion of the cathode catalyst layer based on the Pt / C-TKK catalyst.

[0062] Example 2: Preparation and performance testing of composite catalyst layer membrane electrodes of Pt / C-BY and PtIn / In2O3

[0063] The Pt / C-TKK catalyst in Example 1 was replaced by a Pt / C-BY catalyst (Pt / C-BY, Suzhou Boya Original Nanotechnology Co., Ltd., with a Pt content of 75 wt.%), and the composite catalyst layer membrane electrode of Example 2 of the present invention was prepared according to the method of Example 1, so that the platinum content of the catalyst layer based on indium oxide-supported platinum indium alloy nanocluster catalyst (PtIn / In2O3) was 0.05 mg / cm 2 The platinum content of the cathode catalyst layer of the membrane electrode and the total platinum content of the membrane electrode are 0.35 mg / cm 2 and 0.5mg / cm2 .

[0064] The polarization curve and electrochemical corrosion resistance of the composite catalyst layer membrane electrode prepared in Example 2 were tested according to the method and conditions of Example 1. The test results are as follows: Figure 5 And as shown in Table 2.

[0065] Comparative Example 3: Preparation and performance test of membrane electrode based on Pt / C-BY catalyst

[0066] The Pt / C-TKK catalyst in the comparative example 1 was replaced by the Pt / C-BY catalyst, and a conventional structure membrane electrode based on the Pt / C-BY catalyst was prepared according to the method and conditions of the comparative example 1. The platinum content of the cathode catalyst layer of the membrane electrode and the total platinum content of the membrane electrode were 0.35 mg / cm 2 and 0.5mg / cm 2 The polarization curve and electrochemical corrosion resistance of the product were tested using the method and conditions of Example 1. Figure 5 And as shown in Table 2.

[0067] from Figure 5 From the data in Table 2, it can be seen that the power output performance of the composite catalyst layer membrane electrode prepared in Example 2 is basically consistent with the initial power output performance of the conventional structure membrane electrode with the same platinum loading prepared using the same Pt / C-BY catalyst in Control Example 3, while its electrochemical corrosion resistance under high potential is much better than the latter. After electrochemical aging treatment under the conditions described in Example 1, the composite catalyst layer membrane electrode prepared in Example 2 has a high resistance to electrochemical corrosion at 400mA / cm 2 The potential decay value under the current density is only 33 mV, and the corresponding potential decay value of the membrane electrode prepared in Control Example 3 is 59 mV.

[0068] Example 3: Preparation of composite catalyst layer membrane electrode based on Pt / C-TKK and PtIn / In2O3 catalysts (Pt / C-TKK catalyst layer is located on the PtIn / In2O3 catalyst layer) and performance testing

[0069] Pt / C-TKK and PtIn / In2O3 catalyst slurries and anode catalyst layers were prepared according to the method of Example 1, and the order of spraying the cathode catalyst slurry in Example 1 was changed, that is, the PtIn / In2O3 catalyst slurry was sprayed first and then the Pt / C-TKK slurry was sprayed, so that the platinum content of the catalyst layer based on the PtIn / In2O3 catalyst was 0.05 mg / cm 2 The platinum content of the catalytic layer based on Pt / C-TKK catalyst is 0.35 mg / cm 2 The polarization curve and electrochemical corrosion resistance were tested using the method and conditions of Example 1.

[0070] Example 4: Preparation and performance testing of composite three-layer catalyst membrane electrode based on Pt / C-TKK and PtIn / In2O3 catalysts

[0071] According to the method of Example 1, Pt / C-TKK and PtIn / In2O3 catalyst slurries and anode catalyst layers were prepared. The order of spraying the cathode catalyst slurry in Example 1 was changed to prepare a cathode catalyst layer with a three-layer structure, that is, firstly spraying the PtIn / In2O3 catalyst slurry to form a film, then spraying the Pt / C-TKK slurry to form a film, and finally spraying the PtIn / In2O3 catalyst slurry to form a film. The platinum contents of the three catalyst layers from bottom to top were 0.05 mg / cm 2 , 0.3mg / cm 2 , 0.05mg / cm 2 The polarization curve and electrochemical corrosion resistance were tested using the method and conditions of Example 1.

[0072] Example 5: Preparation and performance testing of composite catalyst layer membrane electrode based on Pt / C-TKK catalyst of Pt / TiO2

[0073] The PtIn / In2O3 catalyst was replaced by a titanium oxide-supported platinum metal nanocluster catalyst (Pt / TiO2, platinum content 30 wt.%), and the composite catalyst layer membrane electrode of Example 5 of the present invention was prepared according to the preparation method and steps of Example 1, and the thickness of the catalyst layer based on the Pt / TiO2 catalyst was adjusted so that the Pt content was 0.1 mg / cm 2 The Pt metal content in other layers remains unchanged, and the polarization curve and electrochemical corrosion resistance are tested using the method and conditions of Example 1.

[0074] Example 6: Preparation and performance testing of composite catalytic layer membrane electrode based on Pt / ITO catalyst

[0075] The PtIn / In2O3 catalyst was replaced by an indium tin oxide (ITO)-supported platinum metal nanocluster catalyst (Pt / ITO, Suzhou Boya Original Nanotechnology Co., Ltd., with a platinum content of 30 wt.%), and the composite catalyst layer membrane electrode of Example 6 of the present invention was prepared according to the preparation method and steps of Example 1, and the thickness of the catalyst layer based on the Pt / ITO catalyst was adjusted so that the Pt content was 0.01 mg / cm 2 The Pt content of other layers remains unchanged. The polarization curve and electrochemical corrosion resistance are tested using the method and conditions of Example 1.

[0076] After cyclic voltammetry aging treatment (potential scanning range: 1.0-1.5V), the composite catalyst layer membrane electrode prepared in Examples 3, 4, 5, and 6 of the present invention has a potential of 400 mA / cm 2The potential decays at current densities were 136mV, 120mV, 154mV, and 179mV, respectively, while the membrane electrode based on the cathode catalyst layer of the Pt / C-TKK catalyst in the control example 1 was 2 The potential decay under current density is 257 mV (Table 1), indicating that the composite catalyst layer membrane electrode prepared in Examples 3, 4, 5, and 6 has much better electrochemical corrosion resistance under high potential than the membrane electrode based on the Pt / C-TKK catalyst cathode catalyst layer.

[0077] Example 7: Preparation and performance testing of composite catalyst layer membrane electrode based on PtCo / C and PtIn / In2O3 catalysts

[0078] The Pt / C catalyst in the double-layer composite cathode catalyst layer was replaced by a carbon-supported PtCo alloy nanocluster catalyst (PtCo / C, the mass percentage of platinum is 40%, the mass percentage of Co is 5%, Tanaka Precious Metals Co., Ltd.), and the cathode catalyst layer spray liquid was prepared according to the method of step 2 in Example 1. A mixture of Pt / C-TKK and a commercially available iridium oxide catalyst was used as an anode catalyst (the mass of the iridium oxide catalyst is 15% of that of Pt / C-TKK), and the anode catalyst layer spray liquid was prepared according to the method of step 2 in Example 1. A composite catalyst layer membrane electrode was prepared according to the preparation method and steps of Example 1, and the Pt platinum metal content of each layer was consistent with that of Example 1. The polarization curve and electrochemical corrosion resistance were tested using the method and conditions of Example 1.

[0079] Comparative Example 4: Preparation and Performance Test of Membrane Electrode Based on PtCo / C Catalyst as Cathode Catalyst Layer

[0080] The PtCo / C catalyst was substituted for the Pt / C-TKK catalyst in the comparative example 1, and the cathode catalyst layer based on the PtCo / C catalyst was prepared according to the method and conditions of the comparative example 1. A mixture of Pt / C-TKK and a commercially available iridium oxide catalyst was used as the anode catalyst (the mass of the iridium oxide catalyst was 15% of that of Pt / C-TKK), and the anode catalyst layer was prepared according to the method in Example 7. The platinum content of the cathode catalyst layer of the membrane electrode and the total platinum content of the membrane electrode were 0.4 mg / cm 2 and 0.5mg / cm 2 , which is consistent with Example 1. The polarization curve and electrochemical corrosion resistance were tested using the method and conditions of Example 1.

[0081] After cyclic voltammetry aging treatment (potential scanning range: 1.0-1.5V), the composite catalyst layer membrane electrode prepared in Example 7 of the present invention has a potential of 400mA / cm 2 The potential decay under current density is 273mV, while the membrane electrode based on PtCo / C catalyst as cathode catalyst layer in comparative example 4 is 400mA / cm 2The potential decay under current density is 468 mV (Table 3), indicating that the composite catalyst layer membrane electrode prepared in Example 7 is much better than the membrane electrode based on the PtCo / C catalyst cathode catalyst layer in terms of electrochemical corrosion resistance under high potential.

[0082] Table 1 shows the membrane electrodes prepared in Example 1, Examples 3-6, Comparative Example 1 and Comparative Example 2 after electrochemical aging treatment at 400 mA / cm 2 The voltage drops under the current density. The experimental condition of the electrochemical aging is to perform cyclic voltammetry scans 5000 times in the potential range of 1-1.5V.

[0083] Table 1

[0084]

[0085]

[0086] Table 2 shows the membrane electrodes prepared in Example 2 and Comparative Example 3 after electrochemical aging at 400 mA / cm 2 and 1500mA / cm 2 The voltage drops under the current density. The experimental condition of the electrochemical aging is to perform cyclic voltammetry scans 5000 times in the potential range of 1-1.5V.

[0087] Table 2

[0088]

[0089] Table 3 shows the membrane electrodes prepared in Example 7 and Comparative Example 4 after electrochemical aging treatment at 400 mA / cm 2 The voltage drops under the current density. The experimental condition of the electrochemical aging is to perform cyclic voltammetry scans 5000 times in the potential range of 1-1.5V.

[0090] Table 3

[0091]

Claims

1. A composite catalyst layer membrane electrode based on heterogeneous catalyst, characterized in that: The composite catalyst layer membrane electrode is composed of a proton exchange membrane and a cathode catalyst layer and an anode catalyst layer respectively covering the surfaces on both sides thereof. The cathode catalyst layer has a multilayer structure, which includes at least one catalyst layer based on a carbon-based material loaded with a platinum-based metal nanocluster catalyst, and also includes at least one catalyst layer based on a metal oxide loaded with a platinum-based metal nanocluster catalyst, wherein the platinum-based metal nanocluster is a platinum or platinum-based alloy nanocluster.

2. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1, characterized in that: The cathode catalyst layer of the composite catalyst layer membrane electrode has a double-layer structure, wherein the first catalyst layer is a catalyst layer based on carbon-based materials loaded with platinum-based metal nanocluster catalysts located above the proton exchange membrane, and the second catalyst layer is a catalyst layer based on metal oxides loaded with platinum-based metal nanocluster catalysts located above the first catalyst layer.

3. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1, characterized in that: The anode catalyst layer of the composite catalyst layer membrane electrode is a catalyst layer based on a carbon-based material loaded with a platinum-based metal nanocluster catalyst.

4. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 3 is characterized in that: The anode catalyst layer also contains iridium oxide catalyst or iridium oxide-metal iridium composite catalyst.

5. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1, characterized in that: The catalytic layer based on carbon-based material-supported platinum-based metal nanocluster catalyst is composited by carbon-based material-supported platinum-based metal nanocluster catalyst and fluoroalkyl sulfonic acid, and the catalytic layer based on metal oxide-supported platinum-based metal nanocluster catalyst is composited by metal oxide-supported platinum-based metal nanocluster catalyst and fluoroalkyl sulfonic acid.

6. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 5, characterized in that: The metal oxide-supported platinum-based metal nanocluster catalyst is a metal oxide nanoparticle-supported platinum-based metal nanocluster catalyst, and the average particle size of the metal oxide nanoparticles is 5-200 nanometers.

7. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 6, characterized in that: The metal oxide nanoparticles are oxide nanoparticles containing at least one of the elements In, Ti, Sn, Sb, Co, and Cu, and the platinum-based metal nanoclusters are Pt or alloy nanoclusters formed by Pt and at least one of the elements In, Ru, and Cu.

8. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 7, characterized in that: The metal oxide nanoparticles are indium oxide or composite metal oxide nanoparticles formed by indium and at least one of Ti, Sn, Sb and Cu elements.

9. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 8, characterized in that: The metal oxide nanoparticle-loaded platinum-based metal nanoclusters are indium oxide-loaded platinum-indium alloy nanoclusters.

10. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 6, characterized in that: In the metal oxide-supported platinum-based metal nanocluster catalyst, on the same metal oxide nanoparticle, the average distance between adjacent platinum-based metal nanoclusters directly contacting the metal oxide nanoparticle is less than 2 nanometers.

11. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1, characterized in that: The cathode catalyst layer of the composite catalyst layer membrane electrode has a three-layer structure, wherein the first catalyst layer is a catalyst layer based on metal oxide nanoparticles loaded with platinum-based metal nanocluster catalysts located on the proton exchange membrane, the second catalyst layer is a catalyst layer based on carbon-based materials loaded with platinum-based metal nanocluster catalysts located on the first catalyst layer, and the third catalyst layer is a catalyst layer based on metal oxide nanoparticles loaded with platinum-based metal nanocluster catalysts located on the catalyst layer based on carbon-based materials loaded with platinum-based metal nanocluster catalysts.

12. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1, characterized in that: In the composite catalytic layer membrane electrode, the platinum content in the metal oxide nanoparticle-loaded platinum-based metal nanocluster catalyst is 20-70%, and the average particle size of the platinum-based metal nanocluster is 1.5 to 5 nanometers.

13. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1 or 6, characterized in that: The thickness of the catalytic layer based on the metal oxide-supported platinum-based metal nanocluster catalyst is 0.05-20 microns.

14. The composite catalyst layer membrane electrode based on heterogeneous catalyst according to claim 1 or 6, characterized in that: The platinum content of the catalyst layer based on the metal oxide supported platinum-based metal nanocluster catalyst is 0.01-1 mg / cm 2 .

15. A method for preparing a composite catalyst layer membrane electrode based on a heterogeneous catalyst as claimed in any one of claims 1 to 12, characterized in that: The catalytic layer based on the carbon-based material-supported platinum-based metal nanocluster catalyst or the metal oxide nanoparticle-supported platinum-based metal nanocluster catalyst is sequentially coated or sprayed on the surface of the proton exchange membrane.

16. The method according to claim 15, characterized in that The slurry used in the coating or spraying comprises a dispersant, a platinum-based metal nanocluster catalyst supported by metal oxide nanoparticles or a platinum-based metal nanocluster catalyst supported by carbon-based materials, and a fluoroalkylsulfonic acid proton migration material.

17. The method according to claim 16, characterized in that The dispersant is selected from at least one of water and alcohol, and the alcohol has 1 to 8 carbon atoms.

18. An application of a composite catalyst layer membrane electrode based on a heterogeneous catalyst according to any one of claims 1 to 12, characterized in that: For use in proton exchange membrane fuel cells.